2008
DOI: 10.1124/dmd.107.018572
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the in Vitro Metabolites of 3,4-Dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (ARQ 501; β-Lapachone) in Whole Blood

Abstract: ABSTRACT:3,4-Dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (ARQ 501; ␤-lapachone) showed promising anticancer activity in phase I clinical trials as monotherapy and in combination with cytotoxic drugs. ARQ 501 is currently in multiple phase II clinical trials. In vitro incubation in fresh whole blood at 37°C revealed that ARQ 501 is stable in plasma but disappears rapidly in whole blood. Our data showed that extensive metabolism in red blood cells (RBCs) was mainly responsible for the rapid disappeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 19 publications
2
30
0
4
Order By: Relevance
“…Using LC-MS coupled to a radioisotope counting system it has been shown that b-lapachone (24) is extensively metabolized in whole blood under in vitro conditions and that the enzymatic activity is located in the RBC. By determining the percent of radioactivity present in protein pellet prepared from whole blood spiked with 14 C b-lapachone, it has been proven that covalent protein binding of b-lapachone and/or its metabolites is a minor contributor in the failure of its detection in blood (Miao et al 2008). …”
Section: Detection Of Labeled Quinones In Biological Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using LC-MS coupled to a radioisotope counting system it has been shown that b-lapachone (24) is extensively metabolized in whole blood under in vitro conditions and that the enzymatic activity is located in the RBC. By determining the percent of radioactivity present in protein pellet prepared from whole blood spiked with 14 C b-lapachone, it has been proven that covalent protein binding of b-lapachone and/or its metabolites is a minor contributor in the failure of its detection in blood (Miao et al 2008). …”
Section: Detection Of Labeled Quinones In Biological Samplesmentioning
confidence: 99%
“…Miao et al (Miao et al 2008) have shown in an in vitro study that b-lapachone (24), a promising anticancer compound, is metabolized by red blood cells (RBCs). While studying its in vitro metabolism in plasma and whole blood, the compound could not be detected with conventional LC-MS.…”
Section: Detection Of Labeled Quinones In Biological Samplesmentioning
confidence: 99%
“…Considering the vulnerability of erythrocytes to oxidative stress, toxicity of ␤L to erythrocytes could be easily foreseeable. The recent finding of Miao et al (2008) that a ␤L derivative could be rapidly sequestered into and metabolized in erythrocytes further supports the specific and selective toxicities of ␤L to erythrocyte. Besides ␤L, many ROS-generating drugs are being developed or marketed for therapeutic uses in cancer and other diseases (Davis et al, 2001;Fibach and Rachmilewitz, 2008;Trachootham et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…While studying the in vitro metabolism of β-lapachone in plasma and whole blood, the compound could not be detected with ESI-LC/ MS. The failure in the detection of β-lapachone in blood by conventional analytical methods led to the use of the radiolabeled 14 C β-lapachone that was necessary in studying its metabolic profile [37].…”
Section: Discussionmentioning
confidence: 99%